Application of Geographical Information System in Landslide Hazard Analysis - Taher T.M.; Omar R.C.; Wahab W.A.; Roslan R.; Solemon B.; Jaapar A.R. (Springer Science and Business Media Deutschland GmbH, 2024)
Landslides can cause disastrous flooding, particularly when streams in the dams are breached by landslide which increases water level and may trigger more slides. This study aims to identify potential landslide zone and its characteristics through landslide hazard mapping using the Geographical Information System (GIS). The importance of precipitation toward the result will also be evaluated using different percentages of influences. Elevation, slope angle, slope aspect, and geology are the variables considered. The susceptibility map was generated by analyzing each factor using the weighted overlay method. The susceptibility map combined with precipitation data generates a Landslide Hazard Map. In the weighted overlay process, assigning different percentages of influence for precipitation resulted in different landslide hazard (LH) zones. The outcome, based on a 55% influence factor, showed that 95.5% of the area was identified as a low hazard while the remaining area was classified as a moderate hazard. In contrast, by using 45% influence, 45.1% area is moderately hazardous followed by lower hazard. Increasing the percentage of influence by more than 55% showed no changes to the LH result. Damage at the dam area will disrupt energy production in the area. Besides urban area, management and monitoring of slope stability in the study area is vital, particularly during unpredictable weather changes. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.